Self-presentation strategies of Chinese CEOs on social media platforms - Guo, Nairui (2024)
This research explores the digital celebrity phenomenon among Chinese CEOs on Weibo, focusing on their self-presentation strategies and interactions with followers. Eight CEOs from various industries were selected based on their public recognition and social media activity. Three types of CEO personal branding strategies emerged through critical visual analysis: professional, person-centered, and hybrid. Professional CEOs primarily focus on industry-related content, positioning themselves as corporate representatives. Person-centered CEOs share aspects of their personal lives to cultivate a relatable image, while hybrid CEOs strike a balance between company-related and personal content. Followers predominantly engage with product-related discussions, expressing gratitude for profits or offering critiques. CEOs in the technology field engage in technical interactions with followers, while those in other fields have limited interaction with fans, often engaging with elite groups or celebrities. This study sheds light on the complex dynamics of CEO digital personal branding and follower engagement on social media platforms.